(untitled) (Andamios, Revista de Investigación Social, 2015)
This paper is an attempt to show how the Andean-borderland communities (Peru, Bolivia and Chile), which were considered through the nineteenth and part of the twentieth century, by the diplomatic and central-state institutions, as heterological, marginal and diplomatically negotiable territories, have reached, since the late twentieth century, a “strategic position” at local, regional, national and international levels, especially on transfrontier scaling. This position has been reached due to emerging processes such as globalization and glocalization. The Andean-highland communities of Ancomarca, Charaña and Visviri are discussed in the scope of this paper.